Formulasi Nugget Ikan Gabus dengan Substitusi Tepung Komposit Kacang Merah dan Tepung Wortel sebagai Pangan Fungsional - Almayda, Anissa Richa; Ma’rifah, Bahriyatul; Muhlishoh , Arwin (ARGIPA (Arsip Gizi dan Pangan), 2024)
Obesity a non-communicable disease closely related to excessive oxidative stress due to an imbalance between prooxidants and antioxidants. Snakehead fish nuggets substituted with red bean composite flour and carrot flour are an alternative food as an effort to prevent this and increase fish consumption. This research aims to determine the effect of substitution of red bean composite flour and carrot flour on the organoleptic properties, nutritional content and antioxidants of snakehead fish nuggets as a functional food. This type of research is experimental using a Completely Randomized Design with four treatments and two repetitions of each treatment, namely the ratio of snakehead fish meat: red bean flour: carrot flour, F0 (250g: 0g: 0g), F1 (200g: 45g: 5g), F2 (175g : 65g : 10g), and F3 (150g : 85g : 15g). Data on nutritional and antioxidant content were analyzed using the ANOVA test and Duncan's advanced test. Organoleptic test data were analyzed using the Kruskal-Wallis test and the Mann-Whitney test. The results of this research are that there is an effect of substitution of red bean composite flour and carrot flour on the hedonic test and hedonic quality, nutritional content and antioxidant content, but it has no effect on the hedonic quality of aftertaste and protein. The best treatment is F3 with nutritional content, namely, 55.02% water; ash 1.99%; protein 13.40%; fat 1.61%; carbohydrates 27.99%, and antioxidants 28.46%; and has met 7.5% of the RDA for obese adults (19-49 years) and claims to protein source based on the general category NLR.